Poly-NIPAM/Fe3O4/multiwalled carbon nanotube nanocomposites for kerosene removal from water. (1st August 2022) - Abdullah, Thamer Adnan; Juzsakova, Tatjána; Le, Phuoc-Cuong; Kułacz, Karol; Salman, Ali D.; Rasheed, Rashed T.; Mallah, Muhammad Ali; Varga, Bela; Mansoor, Hadeel; Mako, Eva; Zsirka, Balázs; Nadda, Ashok Kumar; et al.
Abstract: Multiwalled carbon nanotubes (MWCNTs) were oxidized using a mixture of H2 SO4 and HNO3, and the oxidized MWCNTS were decorated with magnetite (Fe3 O4 ). Finally, poly- N -isopropyl acrylamide- co -butyl acrylate (P-NIPAM) was added to obtain P-NIPAM/Fe/MWCNT nanocomposites. The nanosorbents were characterized by various techniques, including X-ray diffraction, transmission electron microscopy, scanning electron microscopy, thermogravimetric analysis, and Brunauer–Emmett–Teller analysis. The P-NIPAM/Fe/MWCNT nanocomposites exhibited increased surface hydrophobicity. Owing to their higher adsorption capacity, their kerosene removal efficiency was 95%; by contrast, the as-prepared, oxidized, and magnetite-decorated MWCNTs had removal efficiencies of 45%, 55%, and 68%, respectively. The P-NIPAM/Fe/MWCNT nanocomposites exhibited a sorbent capacity of 8.1 g/g for kerosene removal from water. The highest kerosene removal efficiency from water was obtained at a process time of 45 min, sorbent dose of 0.005 g, solution temperature of 40 °C, and pH 3.5. The P-NIPAM/Fe/MWCNTs showed excellent stability after four cycles of kerosene removal from water followed by regeneration. The reason may be the increase in the positive charge of the polymer at pH 3.5 and the increased adsorption affinity of the adsorbent toward the kerosene contaminant. The pseudo second-order model was found to be the most suitable model for studying the kinetics of the adsorption reaction. Graphical abstract: Image 1 Highlights: Poly-NIPAM/Fe3 O4 multiwalled carbon nanotube nanocomposites were synthesized. Their kerosene removal efficiency was 95%, and their sorption capacity was 8.1 g/g. The synthesized nanocomposites demonstrated excellent magnetic properties. The nanocomposites exhibited high regeneration capacity and stable performance.